How India can benefit from FDI: lessons from China - Ilan Strauss; Vasiliki Mavroeidi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
This Perspective responds to Sauvant and Allman's Perspective about what India can learn from China. Their Perspective focuses on FDI attraction and liberalization. However, the better lesson from China is to use industrial policies. This Perspective explores India's options, given the restrictions placed on their use under international agreements.
Keywords: 330